Model sistem informasi geografis pariwisata menggunakan reuse method - henderi henderi; Andrian Saputra; Didik Setiyadi (Direktorat Riset dan Pengabdian Pada Masyarakat (DRPM) Universitas Bina Darma, 2020)
Information about tourism sites in Tangerang Regency is inadequate. Tourists have difficulty in obtaining information about tourist attractions. This study propose a model of tourism geographic information system (GIS) to make help tourists to find and obtain information about tourism in Tangerang Regency easier. In this research, activities consist of two stages, namely: data collection and system design. Data collection activities carried out by observation, interviews, and literature study. While the GIS model is designed with Unified Modeling Language, reuse method, and prototype. The final result of this research is a model of tourism geographic information system in the form of use case diagrams, activity diagrams, class diagrams and prototype user interfaces. The test results showing that the model produced has a score of 72.1 with a good predicate. This shows that the resulting model is in accordance with needs and can be used as a basis in building a tourist geographic information system.